Subacute hemorrhagic pericardial tamponade after COVID-19 infection mimicking carcinomatous pericarditis: a case report - Yamamoto, Hiroyuki; Kume, Nao; Hashimoto, Katsuya; Isogai, Jun; Kuwabara, Takuya; Noguchi, Masayuki; Murayama, Hiroyuki; Hashimoto, Toru; Ogino, Hidemitsu (Frontiers in Cardiovascular Medicine, 2024)
Background Coronavirus disease (COVID-19)-associated acute pericarditis has recently received much attention owing to its high frequency associated with pericardial tamponade (PT), showing unfavorable prognosis. However, early diagnosis and treatment remain challenging in cases of non-specific signs and symptoms. Case presentation A 64-year-old man was admitted to our hospital for acute osteomyelitis of the toes and was properly treated with antimicrobial agents. Three days after admission, the patient developed mild COVID-19 without pneumonia, for which early anti-COVID-19 agents were initiated. Nevertheless, the patient developed hemorrhagic PT due to acute pericarditis 2 weeks later, which was confirmed by cardiac magnetic resonance, requiring an urgent pericardiocentesis. Although cytological analysis of the hemorrhagic pericardial fluid strongly suggested adenocarcinoma, the atypical cells were eventually proven to be mesothelial cells with reactive atypia. Furthermore, lymph nodes swelling with abnormal 2-[18F]-fluoro-2-deoxy-D-glucose accumulation on imaging were suggestive of malignancy. However, biopsy examination revealed multiple non-caseating granulomas in the lymph node, unlikely due to malignancy. Eventually, the temporal association of the preceding COVID-19 with the occurrence of subacute PT without other identifiable cause led to a final diagnosis of COVID-19-associated acute pericarditis. With anti-inflammatory and corticosteroids treatment, the patient's symptoms involving the pericardial structure and function were completely resolved along with improvements in size of the affected lymphadenopathies. Conclusions We encountered a unique case of COVID-19-associated acute pericarditis exhibiting hemorrhagic PT. This case underscores the residual risk of delayed pericardial involvement even in patients with mild COVID-19 who receive early treatment, and the recognition that COVID-19 may cause various cytomorphological and histological features. Additionally, the importance of considering this rare entity as a cause of hemorrhagic pericardial effusions should be highlighted.